The Cross-Cultural use of the Kirton Adaption- Innovation Inventory: A Further Exploration - Clapp, PhD, Ray; Ruckthum, PhD, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
Abstract English language measures such as the bipolar scale of cognitive style (Kirton, 2005) are not easily understood by people within diverse cultures and languages where English is spoken as a second language. Particularly the scoring of opposites when many items represent each end of the dimensional continuum and where items that represent one of the poles are reverse scored to produce the final score. Understanding can be improved by using a translation of item meaning into the target language. However, a more efficient method is the use of items with bipolar scoring scales to resolve the problem of accurate recognition and scoring of opposites while at the same time eliminating the scoring anchor and any associated social desirability contamination. Keywords : bipolar scales, translation, negative items